2023
DOI: 10.1002/nme.7190
|View full text |Cite
|
Sign up to set email alerts
|

A novel numerical strategy for modeling the moving boundary value problem of electrochemical machining

Abstract: This work presents a new numerical approach to efficiently model the cathode's moving surface in the moving boundary value problem of electrochemical machining. Until recently, the process simulation with finite elements had the drawback of remeshing required by the changing surface geometries. This disadvantage was overcome by an innovative model formulation for the anodic dissolution that utilizes effective material parameters as well as the dissolution level as an internal variable and, thereby, does not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…1. Concept of the dissolution process with iron-based dissolution, see also [6,7]: dissolution variable 𝒅𝒅 varying between 𝒅𝒅 = 𝟎𝟎 in the metal and 𝒅𝒅 = 𝟏𝟏 in the electrolyte.…”
Section: The Concept Of Effective Parameters Using the Dissolution Le...mentioning
confidence: 99%
See 2 more Smart Citations
“…1. Concept of the dissolution process with iron-based dissolution, see also [6,7]: dissolution variable 𝒅𝒅 varying between 𝒅𝒅 = 𝟎𝟎 in the metal and 𝒅𝒅 = 𝟏𝟏 in the electrolyte.…”
Section: The Concept Of Effective Parameters Using the Dissolution Le...mentioning
confidence: 99%
“…The original paper [6] additionally considers a thermally coupled system. There also a more detailed description of the effective parameter approach can be found, which is also later used for the consideration of a relocatable cathode in terms of a moving boundary value problem [7]. Due to simplicity, the additional thermal problem is skipped, here.…”
Section: The Concept Of Effective Parameters Using the Dissolution Le...mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the presented model utilizes a second order damage tensor and a finite strain formulation and is applied to purely mechanical problems. In future, the anisotropic damage modeling can be incorporated into multiphysical process simulations (e.g., [12,13]) and medical applications (e.g., [14]).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, scholars at home and abroad have carried out a lot of scienti c research. Velden used numerical simulation method to simulate and analyze the cathode pro le, which shortened the cathode development cycle [15]. Mishra Technology studied the cathode structure based on the ow eld simulation model of transverse groove ECM, and concluded that symmetrical and uniform placement of cathode holes can improve the gap ow eld homogeneity [17].…”
Section: Introductionmentioning
confidence: 99%